PERAN PENDIDIKAN KEWARGANEGARAAN (PKN) DALAM MENGATASI KASUS BULLYING PADA PESERTA DIDIK - Sari, Nurmala; Devra, Desi Devrika (Komunitas Manajemen Kompetitif, 2024)
Abstract: Citizenship Education (Civics) in schools is very important in relation to the character building of students and a strategic role in increasing the potential of students to become good and democratic citizens based on Pancasila and the 1945 Constitution. this study aims to explore the role of Civics in overcoming bullying in schools, especially in optimizing the application of Civics in preventing bullying behavior. This research is a qualitative study using the library research method. The result of this study is that civic education has an important role in overcoming bullying, both directly and indirectly. Civic education can help students develop state awareness, have an awareness of their rights and obligations as citizens, and have the ability to deal with various situations, including bullying situations. Keywords: role, civic education, bullying